BISNIS PERSEWAAN KELUARGA DALAM NASKAH DRAMA TELEVISI KAZOKU KASHIMASU â€“ FAMILY COMPLEX: KAJIAN SOSIOLOGI SASTRA - Maya Pradityasari (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
The turning of Japaneses family system Ie into Kazoku Kaku affected negatively on the processof interaction and communication within the members of the family, with the neighborhood and amongthe members of society. In turn, it brought about the idea of family rental business in Japan. Nipon TVaired a television drama which portrayed this social phenomenon entitled â€œKazoku Kashimasu-familyComplex. This article is exploring the cause of the emergence of this phenomenon as seen the TV drama.This study applied sociological approach. The data in this research are scenes and conversations in a playentitled â€œKazoku Kashimasu-family Complexâ€. The analysis shows that one factor causing thephenomenon of family rental business is the divorce that resulted in the single parent or a single parent.Another factor is the familyâ€™s disharmony caused by busyness, self-centered nature, the cold war, and theculture of silence. The change of Japanese family system into the family system Tanshin Setai is reflectedin the life of one of the characters in the television drama â€œKazoku Kashimasuâ€. The representation offamily rental business is reflected by a company called Family Romance founded by Shuji as the maincharacter. The Family Romance is a rental business family which proved a service of rental family for awedding reception, a commemoration of those who have died called Shinobukai, the purposes of schoolenrollment at the famous school, and for a protest to a school on cases of bullying.Keywords : sistem keluarga Jepang, persewaan keluarga, drama televisi, sosiologi sastra